2016
DOI: 10.1055/s-0042-104055
|View full text |Cite
|
Sign up to set email alerts
|

Senology in Gynaecology Specialist Training: a Baseline Survey from 2014

Abstract: Einleitung: Eine qualifizierte Weiterbildung in der Senologie ist für das Fortbestehen einer guten und qualitativ hochwertigen Patientenversorgung essenziell. Um den Ansprüchen der Weiterbildungsassistenten und der medizinischen Infrastruktur gerecht zu werden, ist es notwendig, die Weiterbildungsqualität regelmäßig zu erfassen, um diese entsprechend anpassen und optimieren zu können. Methodik: Zur Erfassung der Weiterbildungsqualität haben wir einen 10 Items umfassenden Online-Fragebogen entwickelt. Die bunde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
1
2
0
1
Order By: Relevance
“…However, our study showed that the quality of surgical training in OBGYN was only rated as satisfactory to sufficient, with trainers giving an average rating of 2.7 and trainees giving a rating of 3.7 on a scale from 1 to 6. This finding is in line with previous studies that have evaluated training in OBGYN [ 5 , 7 ] or in senology [ 6 ] and confirms that trainees generally evaluate surgical training more negatively than trainers [ 5 ]. Like many other European countries, Germany maintains a logbook to document performed surgical procedures during OBGYN training [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, our study showed that the quality of surgical training in OBGYN was only rated as satisfactory to sufficient, with trainers giving an average rating of 2.7 and trainees giving a rating of 3.7 on a scale from 1 to 6. This finding is in line with previous studies that have evaluated training in OBGYN [ 5 , 7 ] or in senology [ 6 ] and confirms that trainees generally evaluate surgical training more negatively than trainers [ 5 ]. Like many other European countries, Germany maintains a logbook to document performed surgical procedures during OBGYN training [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Dadurch können einzelne Ergebnisse nur mit äußerster Vorsicht als Grundlage weiterführender Überlegungen interpretiert werden. Trotzdem ist die Verteilung sowohl über alle Versorgungsarten und Positionen ausreichend homogen und spiegelt mit 437 Teilnehmern eine übliche Gruppengröße einer Kohorte im Vergleich zu den für die Einordnung recherchierten Arbeiten zur Arbeitsbelastung wider [16][17][18][19]. Durch kleine Stichproben sind Verzerrungen möglich.…”
Section: Stärken Und Limitationen Der Vorliegenden Umfrageunclassified
“…Nevertheless, the distribution was sufficiently homogeneous across all types of in-hospital care and across all levels of medical training. With 437 respondents, the number of participants in our study corresponds to the usual group size of cohorts reported in articles on workloads used for comparative analysis [16][17][18][19]. The small sample sizes mean that bias is possible.…”
Section: Strengths and Limitations Of This Surveymentioning
confidence: 99%
“…Even in Germany as recently as 30 years ago, gynecologists were effectively "competing" with surgeons over the treatment of breast conditions, including cancer, and a similar situation still occurs in Poland [5]. Although, the role of surgeons in treating women with breast cancer in Germany remains important, it is limited to multimodal treatments (local recurrence, distant metastases, and supportive procedures in radiation therapy, chemotherapy, and hormone therapy) [6].…”
mentioning
confidence: 99%